A case analysis of enabling continuous software deployment through knowledge management. (June 2018) - Colomo-Palacios, Ricardo; Fernandes, Eduardo; Soto-Acosta, Pedro; Larrucea, Xabier
Abstract: Continuous software engineering aims to accelerate software development by automating the whole software development process. Knowledge management is a cornerstone for continuous integration between software development and its operational deployment, which must be implemented using sound methodologies and solid tools. In this paper, the authors present and analyse a case study on the adoption of such practices by a software company. Results show that, beyond tools, knowledge management practices are the main enablers of continuous software engineering adoption and success.